A comprehensive hydrometallurgical recycling approach for the environmental impact mitigation of EoL solar cells. Issue 6 (December 2021) - Luo, Miaosi; Liu, Fangyang; Zhou, Zhe; Jiang, Liangxing; Jia, Ming; Lai, Yanqing; Li, Jie; Zhang, Zongliang
Abstract: With the rapid increase of the installed capacity of crystalline silicon photovoltaic (PV) modules, the number of used modules that reach their End of Life (EoL) is accumulating dramatically and it is expected to pose significant environmental hazards. To solve this upcoming issue, this research investigated a comprehensive hydrometallurgical recycling process for crystalline silicon (C-Si) solar cells with regard to the problems of low element separation efficiency, inadequate component recovery rate, and deficient environmental considerations in the current recycling processes. Appropriate hydrometallurgical recovery processes were designed to recover valuable elements and entrap hazardous material lead (Pb) while properly treating wastewater from the recycling process. Nitric acid (HNO3 ) is an effective choice for elemental leaching from the waste, with 98.12% and 99.57% simultaneous leaching rates of silver (Ag) and aluminum (Al), respectively. The overall recovery rate of Ag was 96.13% using the hydrochloric acid (HCl) precipitation-ammonia solubilization-hydrazine process route. The purity of Ag after reduction was 99.8%. The silicon nitride (SiNx ) and silicon phosphide (Si3 P4 ) layers on the surface of the silicon wafer can be completely etched and removed by low-concentration HCl, and the product obtained is pure silicon. Most importantly, heavy metal elements such as Pb were captured to prevent potential damage to the environment and human health. Graphical Abstract: ga1 Highlights: Efficient separation and recovery of Si, Ag, and Al from EoL solar cells. The purity of reduced silver powder is as high as 99.8%. Etching of silicon wafers by low concentration HF. Leachate is recycled and harmful element Pb was effectively removed. The process is suitable for large-scale production.